Urinary microbiota and bladder cancer: A systematic review and a focus on uropathogens. (November 2022) - Yacouba, Abdourahamane; Tidjani Alou, Maryam; Lagier, Jean-Christophe; Dubourg, Grégory; Raoult, Didier
Abstract: The higher incidence of bladder cancer in men has long been attributed to environmental factors, including smoking. The fact that the sex ratio of bladder cancer remains consistently weighted toward men despite the remarkable increase in the prevalence of smoking among women suggests that other risk factors influence the incidence rates of bladder cancer. These factors may include the urinary microbiota. In this study, we provide a review of recent literature regarding the association between bladder cancer and changes in the urinary microbiota, with a focus on the potential role of uropathogens in the microbiota and sex in bladder cancer. Four databases were systematically searched up to 31 March 2021 to identify human case–controlled studies that evaluated the relationship between urinary microbiota and bladder cancer. We combined bacterial taxa that were significantly higher or lower in the bladder cancer group in each study in the urine (voided and catheterized) and tissue samples. Findings from sixteen eligible studies were analyzed. The total sample size of the included studies was 708 participants, including 449 (63.4 %) bladder cancer patients and 259 (36.6 %) participants in the control group. When considering only the taxa that have been reported in at least two different studies, we observed that with regards to neoplastic tissues, no increased taxa were reported, while Lactobacillus (2/5 of the studies on tissue samples) was increased in nonneoplastic-tissue compared to neoplastic-tissues at the genus level. In catheterized urine, Veillonella (2/3 of the studies on catheterized urine) was increased in bladder cancer patients compared to the control groups at the genus level. In voided urine, Acinetobacter, Actinomyces, Aeromonas, Anaerococcus, Pseudomonas, and Tepidomonas were increased in the bladder cancer patients, while Lactobacillus, Roseomonas, Veillonella were increased in the control groups. Regarding gender, the genus Actinotignum was increased in female participants while Streptococcus was increased in male participants at the genus level. Regarding potential uropathogens in the urinary microbiota, Escherichia-Shigella provided conflicting results, with both showing higher and lower levels in the bladder cancer groups. However, the family Enterobacteriaceae was lower in the bladder cancer groups than in the control groups. In conclusion, there is no consensus on what taxa of the urinary microbiota are associated with bladder cancer according to the sample type. Findings on the potential role of uropathogens in the urinary microbiota in bladder cancer remain inconsistent. Due to the limited number of studies, further studies on urinary microbiota and bladder cancer are needed to address this issue. Given that all publications concerning the urinary microbiota and bladder cancer have been performed using 16S rRNA gene sequencing, we propose that polyphasic approaches, including culture-dependent techniques, may allow for a more comprehensive investigation of the urinary microbiota associated with bladder cancer.